The Effect of Training Using Demonstration Methods on Community Knowledge About Mitigation and Evacuation of Disaster Victims - Yusuf, Zuhriana K; Suleman, Ibrahim; Hunawa, Rachmawaty D; Rahma, St (Jambura Nursing Journal, 2024)
Knowledge that is used sustainably is an urgent need, especially considering the threat of natural disasters that can arise anytime and anywhere. Therefore, people need basic capital to save themselves from disasters, namely emergency response capabilities to disasters and sufficient resources. The aim of the research is to analyze the effect of training using the demonstration method on public knowledge about mitigating and evacuating disaster victims. The method used is observational analytical research. The population is the people of Lopo village, Batudaa Pantai District with a sampling technique, namely accidental sampling, namely 19 people. The total sample was 67 respondents. Data collection was carried out using instruments based on the Knowledge questionnaire with pretest and posttest methods after training and demonstrations. Data analysis was carried out using paired sample T-Test statistical analysis of respondents from the Lopo Village community. The results of the analysis of the influence of training using the demonstration method on public knowledge regarding mitigation and evacuation of disaster victims obtained a value of Ï = 0.000 (Ï = 0.05) so that there is an influence between the two variables. The conclusion is that there is an influence of training using the demonstration method on community knowledge regarding mitigation and evacuation of disaster victims in the Lopo Village community.